Conflict Kitchen and Enemy Kitchen: Socially Engaged Food Pedagogy. (3rd July 2019) - Shin, Ryan; Bae, Jaehan
Abstract : In this article, we examine food-engaged art practice and its artistic and pedagogical possibilities. First, we describe the precedents of socially engaged food art practices and provide a detailed account of Conflict Kitchen and Enemy Kitchen, from which we envision new pedagogical possibilities to embrace food and cooking as socially engaged art. In the second part of the study, we discuss the two kitchens through Deleuzian concepts such as nomadism, agencément, and becoming-others, to explore and encourage a shift from the pedagogy of being to the pedagogy of becoming. We argue that art educators pay attention to the becoming pedagogy as a rhizomatic, transforming, and unresting status of socially engaged learning, challenging the being pedagogy of the structured, goals-oriented, and standard-based learning.